Health status of Medicare-enrolled autistic older adults with and without co-occurring intellectual disability: An analysis of inpatient and institutional outpatient medical claims. (January 2021) - Gilmore, Daniel; Harris, Lauren; Longo, Anne; Hand, Brittany N
Little is known about the extent to which the healthcare needs of autistic older adults with intellectual disability differ from autistic older adults without intellectual disability. We conducted a cross-sectional retrospective cohort study of Medicare claims data from 2016 to 2017 to compare the prevalence of physical and mental health conditions among autistic older adults (age 65+ years) with intellectual disability ( N  = 2054) to autistic older adults without intellectual disability ( N  = 2631). Medicare claims data consisted of records from inpatient hospitalizations and institutional outpatient visits (i.e. visits to hospital outpatient departments, rural health clinics, renal dialysis facilities, outpatient rehabilitation facilities, Federally Qualified Health Centers, and community mental health centers). Examination of the largest between-group differences revealed that autistic older adults with intellectual disability had 350% greater odds of epilepsy (odds ratio = 4.5, 95% confidence interval = 3.9–5.2), 170% greater odds of osteoporosis (odds ratio = 2.7, 95% confidence interval = 2.3–3.2), and 100% greater odds of gastrointestinal conditions (odds ratio = 2.0, 95% confidence interval = 1.8–2.2) but 80% lower odds of attention deficit disorders (odds ratio = 0.2, 95% confidence interval = 0.1–0.3), 70% lower odds of substance use disorders (odds ratio = 0.3, 95% confidence interval = 0.2–0.4), and 60% lower odds of suicidal ideation or intentional self-injury (odds ratio = 0.4, 95% confidence interval = 0.3–0.6). These findings highlight the importance of developing tailored health management strategies for the autistic older adult population as a function of intellectual disability status. Lay abstract: Little is known about the extent to which the healthcare needs of autistic older adults with intellectual disability differ from autistic older adults without intellectual disability. Our study is the first, to our knowledge, to use US national data to compare physical and mental health conditions among autistic older adults with and without intellectual disability. The data analyzed in this study consisted of records from inpatient hospitalizations as well as "institutional outpatient" healthcare visits, which include visits to hospital outpatient departments, rural health clinics, renal dialysis facilities, outpatient rehabilitation facilities, Federally Qualified Health Centers, and community mental health centers. Autistic older adults with intellectual disability were significantly more likely to have thyroid disorders, epilepsy, respiratory infections, gastrointestinal conditions, osteoporosis, cognitive disorders, and schizophrenia/psychotic disorders. In contrast, autistic older adults without intellectual disability were significantly more likely to have obesity, diabetes, high blood pressure, cerebrovascular disease, chronic obstructive pulmonary disease, arthritis, back conditions, attention deficit disorders, substance use disorders, and suicidal ideation or intentional self-injury. These findings highlight the importance of developing distinct, tailored health management strategies for the autistic older adults with and without intellectual disability.